Reproductive ecology and territorial behavior of Boana goiana (Anura: Hylidae), a gladiator frog from the Brazilian Cerrado - Dias, Tailise M.; Prado, Cynthia P. A. [UNESP]; Bastos, Rogerio P. (Soc Brasileira Zoologia, Univ Federal Parana, 2021)
Anuran males and females adopt different reproductive and behavioral strategies in different contexts. We investigated the reproductive ecology and territorial behavior of the treefrog Boana goiana (B. Lutz, 1968) from the Brazilian Cerrado. We hypothesized that competitor density/proximity would increase the behavioral responses of B. goiana males, and that mating would be assortative. We also tested if the number of eggs correlates with female size and if there is a trade-off between clutch size and egg size. We conducted two territoriality experiments to test the effects of male size, competitor proximity and competitor density. Larger males called more in the presence of a second male. In the second experiment, the largest males emitted more calls and the distance to the nearest male increased as resident males called more. In both experiments, the number of calls was influenced by either male size or spacing between males. Some males behaved as satellites, probably to avoid fights. Our analyses indicate that females choose males with similar sizes to their own, corroborating our hypothesis of size-assortative mating. We found no relationships between female size and clutch size/volume, and between egg size and number of eggs per clutch. We also report multiple spawning for this species. The low incidence of physical combats and the spacing pattern indicate that this species relies almost solely on calls to resolve contests, which could be explained by low motivation, or simply because males avoid combats to decrease injury risks. Thus, acoustic or even multimodal communication seems crucial for social interactions of B. goiana.
Keywords: Clutch size; acoustic communication; assortative mating; male competition; aggressive interactions; arrival dynamics